011 Outcome of children on the UK national prioritised paediatric registration tier. (12th September 2022) - Dixit, Shweta; Taylor, Rhiannon; Whitney, Julie; Hartley, Jane; Attia, Magdy; Mirza, Darius; Rajwal, Sanjay; Watson, Sarah; Isaac, John; Manas, Derek; Heaton, Nigel; Dhawan, Anil; et al.
Abstract : Introduction: In April 2020 weekly teleconferences were established involving adult and paediatric representation from all 7 UK liver transplant (LT) centres and NHS England to discuss and maintain a national LT service during the COVID19 pandemic. Objective criteria to prioritise adult patients of high clinical urgency for prioritised access to LT were established. In lieu of such criteria for paediatric patients all three paediatric centres agreed to prioritise individual paediatric patients with chronic liver disease who were clinically deteriorating by consensus. A process to formally nationally prioritise clinically deteriorating paediatric patients was successfully introduced in October 2020. We report on the utilisation of the tier and outcome of these patients at a national level. Methods: Patients from all 3 paediatric LT centres registered on the newly established national prioritised paediatric registration tier from October 2020-October 2021 were included. Demographic, clinical and laboratory data were collected and analysed. Results: Since the introduction of the prioritization tier for children there were eight UK elective applications and all approved registrations. Mean age of patients registered was 5 years (range, 0–15). All patients were listed for LT prior to prioritisation except patient 5 who was listed for liver-small bowel transplant before being prioritised for isolated LT. Indications for prioritization were hepatocellular carcinoma (1), acute decompensation due to portal hypertension (2), encephalopathy (3), sepsis (1), acute kidney injury (1). At time of prioritisation median values and range of alanine aminotransferase, albumin, total bilirubin, INR and platelets were 95 IU/L (23–453), 25 g/L (16–39), 196 micromol/L (10–553), 1.6 (0.97–2.27) and 75 x109 (41–188), respectively. Median waiting time to transplant after prioritisation was 10 days (range, 3–37). All patients received a graft from a DBD donor and are all well at home. Median length of post-transplant ICU stay was 9 days (3–62) and total length of hospital stay was 56 days (27–85). Data on demographics and LT are listed on table 1 . Conclusion: The national paediatric prioritisation tier, introduced during the COVID19 pandemic, has been a pivotal initiative for the UK paediatric LT program, showcasing national collaboration. All patients underwent a LT successfully within a short time from prioritisation with 100% patient and graft survival. The intention is to maintain this prioritised paediatric tier following the pandemic.